2021
DOI: 10.3390/s21144928
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Computer-Assisted Diagnosis System for Early Assessment of Renal Cancer Tumors

Abstract: Renal cell carcinoma (RCC) is the most common and a highly aggressive type of malignant renal tumor. In this manuscript, we aim to identify and integrate the optimal discriminating morphological, textural, and functional features that best describe the malignancy status of a given renal tumor. The integrated discriminating features may lead to the development of a novel comprehensive renal cancer computer-assisted diagnosis (RC-CAD) system with the ability to discriminate between benign and malignant renal tum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 48 publications
(72 reference statements)
0
9
0
Order By: Relevance
“…MLP model is a feed-forward artificial neural network (ANN) model that is applicable to a non-linear inseparable issue; Almubark et al demonstrated the predictive value of this approach in their previous study ( 26 ). The generalization and efficacy of this method have been widely confirmed in several papers ( 27 29 ). Given these characteristics, we also established an MLP classifier for the recurrence of PMA and achieved satisfactory levels of predictive performance in a test cohort.…”
Section: Discussionmentioning
confidence: 75%
“…MLP model is a feed-forward artificial neural network (ANN) model that is applicable to a non-linear inseparable issue; Almubark et al demonstrated the predictive value of this approach in their previous study ( 26 ). The generalization and efficacy of this method have been widely confirmed in several papers ( 27 29 ). Given these characteristics, we also established an MLP classifier for the recurrence of PMA and achieved satisfactory levels of predictive performance in a test cohort.…”
Section: Discussionmentioning
confidence: 75%
“…These temporal changes enable the construction of contrast-enhancement slope. This slope is calculated by getting the gray-level intensity change rate over the time period between the two phases [ 43 , 44 ]. HGG tumors might demonstrate higher and faster slopes than those of LGG tumors.…”
Section: Methodsmentioning
confidence: 99%
“…Artificial intelligence (AI) plays an important role in diagnosing diseases such as breast cancer [40], liver cancer [99], renal cancer [100], brain cancer [101], heart failure [102], and recently COVID-19 [103,104]. It is also possible to utilize AI to detect and anticipate massive epidemics.…”
Section: Ai-based Systems For Diagnosing Covid-19mentioning
confidence: 99%